The taxonomic status of the shrew of St. Lawrence Island, Bering Sea (Mammalia: Soricidae) ... - Rausch, Robert L; Rausch, V R (Biological Society of Washington, 1995)
(Uploaded by Plazi from the Biodiversity Heritage Library) No abstract provided. ...